Enhancing professional abilities of university students through digital educational interventions: a study in Kazakhstani universities - Kurakbayeva, Aigul; Xembayeva, Saule (Frontiers in Education, 2025)
This study investigates enhancing professional abilities among university students in Kazakhstan through digital educational interventions. These abilities are increasingly crucial in a labor market shaped by rapid technological advancements. The research included 520 students from Toraighyrov University and L.N. Gumilyov Eurasian National University. The research employed a systematized methodology that involved a literature review of existing studies to identify key themes related to students’ professional abilities and rigorous testing and correlation analyses using SPSS software. The educational interventions consisted of interactive online classes, a 12-week MOOC in “Psychology,” and a 16-week course on managing learning processes using distance education technologies. The interventions significantly improved students’ performance on cognitive ability tests, enhanced creativity-related task outcomes, increased motivation, and strengthened professional orientation. These gains are supported by paired t-tests and align with theoretical frameworks such as Cattell’s theory and Self-Determination Theory. This study underscores the effectiveness of digital tools and interactive platforms in developing cognitive and non-cognitive skills, which aligns with contemporary educational reforms and studies in Kazakhstan.